The orbitofrontal cortex processes neurofeedback failure signals - Paret, Christian; Ende, Gabriele; Schmahl, Christian (Behavioural brain research, 2019)
Receiving feedback from neural activity, dubbed neurofeedback, can reinforce brain self-regulation. In a real-time functional magnetic resonance imaging (fMRI) experiment, healthy participants received amygdala neurofeedback via a visual brain-computer interface. The brain response to signals of reward and failure was modeled. In contrast to previous analyses, we take into account feedback that immediately preceded these signals. That means we tested whether responses were modulated while participants observed sequent reward and failure signals. The orbitofrontal cortex (OFC) showed a negative Blood Oxygenation Level Dependent (BOLD) response to failure signals, when they were preceded by more failure signals. When failure signals were preceded by reward, in contrast, the response was less pronounced. The results suggest weighted processing of neurofeedback value in the OFC. Learning to self-regulate the brain with neurofeedback may involve similar neural networks as the learning of goal-directed action.
Gesehen am 16.07.2019